Naucno-metodiceskoe obespecenie sistemy distancionnogo obucenija - Cistjakov, V. A.; Filippov, S. S.; Knjazeva, N. P. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
Constantly growing volume of the information which the student should remember, understand and reproduce, mean revision of all process of training from positions of the advanced achievements of science and technology. Development of local and global electronic networks, multimedia means of training, a prompt computerization es-sentially change the contents and an orientation of high school education, including in area of physical culture. Transition to the state educational standards of the third generation and sharp increase in time allocated for inde-pendent work, naturally mean development of probable ways of realization of these processes.